1998
DOI: 10.1037/1040-3590.10.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Satisfaction With Appearance Scale: Assessing body image among burn-injured patients.

Abstract: SWAP) is a 14-item questionnaire, assessing both the subjective appraisal and social-behavioral components of body image among bum survivors. Burn survivors requiring hospitalization (n = 165} completed a packet of psychometric instruments, including the SWAP at 1-week postdischarge. The SWAP demonstrated a high level of internal consistency (Cronbach's alpha, r. = .87; the mean interitem correlation, r,, = .32, the mean itemtotal correlation, rit = .53). Eighty-four participants were retested approximately 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 34 publications
1
101
0
7
Order By: Relevance
“…Many different aspects of the post burn environment can be distressing at different stages, such as painful dressing changes and aversive physical therapy procedures (4), significant alterations in body image during the rehabilitation period (18), as well as stigmatizing reactions from others (60). It is notable that our inhospital Anxiety or Hyperarousal factors predict long-term distress, given previous work suggesting that poststressor sympathetic activation is a predictor of later PTSD (61,62).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Many different aspects of the post burn environment can be distressing at different stages, such as painful dressing changes and aversive physical therapy procedures (4), significant alterations in body image during the rehabilitation period (18), as well as stigmatizing reactions from others (60). It is notable that our inhospital Anxiety or Hyperarousal factors predict long-term distress, given previous work suggesting that poststressor sympathetic activation is a predictor of later PTSD (61,62).…”
Section: Discussionmentioning
confidence: 90%
“…Body image dissatisfaction appears common in patients with burn injuries (18). Sleep disturbances occur frequently among in-patients with burns, e.g., nightmares in 39% and significant sleep problems in 75% (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…However, these cautions seem to have had rather little impact on methodological choices made in many applications of EFA. Articles published in recent years in respected journals (e.g., Beidel, Turner, & Morris, 1995;Bell-Dolan & Allan, 1998;Brown, Schulberg, & Madonia, 1995;Collinsworth, Strom, & Strom, 1996;Copeland, Brandon, & Quinn, 1995;Dunn, Ryan, & Paolo, 1994;Dyce, 1996;Enns & Reddon, 1998;Flowers & Algozzine, 2000;Gass, Demsky, & Martin, 1998;Kier & Buras, 1999;Kwan, 2000;Lawrence et al, 1998;Osman, Barrios, Aukes, & Osman, 1995;Shiarella, McCarthy, & Tucker, 2000;Yanico & Lu, 2000) continue to follow the Little Jiffy approach in whole or in part, undoubtedly yielding some potentially misleading factor analytic results. Repeated use of less than optimal methods reinforces such use in the future.…”
mentioning
confidence: 99%
“…[36] Finally, clinically significant symptoms of depression were reported by 23% in a US sample [37] and 27% in a British sample [38] at 2 years; and 20% of Greek patients with burn injuries had a depressive disorder at 2years. Malt et al and Patteron et al (62,18) reported that anxiety and depression were the most prevalent disturbances in burn patients at follow-up.It was found that symptoms of depression and anxiety generally occurred together, With prevalence rats between 25% and 65% one yr post burn, and that most symptoms subsided after that period (18) In more recent studies published after 1990, depression prevalence rates vary between 2% (63) and 53% (64) the 1 st month after the burn, and between 13% (65) and 34% (64) at 12 momth post burn.…”
Section: Psychiatric Manifestation In Post Burn Patientsmentioning
confidence: 99%